2002
DOI: 10.1046/j.1537-2995.2002.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

IgG1 and IgG3 anti‐D in maternal serum and on the RBCs of infants suffering from HDN: relationship with the severity of the disease

Abstract: The proportion of IgG3 anti-D relative to the total anti-D IgG on infants' RBCs is only one- third of the proportion present in maternal serum. The study of the correlations between the amount of IgG1 anti-D and IgG3 anti-D and the severity of HDN suggests that IgG1 anti-D are more important than IgG3 anti-D in the pathogenesis of fetal anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
3
18
0
1
Order By: Relevance
“…An explanation for this finding is that it is easier for IgG1 subclass to cross the placenta than for IgG3 subclass, which causes more IgG1 in the sera of infants than IgG3. This is consistent with previous studies, which found that the proportion of IgG3 on infants' RBC is about three times lower than in maternal sera [3] . The concentration level of IgG4 showed no significant difference between HDN group and study infants without HDN.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…An explanation for this finding is that it is easier for IgG1 subclass to cross the placenta than for IgG3 subclass, which causes more IgG1 in the sera of infants than IgG3. This is consistent with previous studies, which found that the proportion of IgG3 on infants' RBC is about three times lower than in maternal sera [3] . The concentration level of IgG4 showed no significant difference between HDN group and study infants without HDN.…”
Section: Discussionsupporting
confidence: 94%
“…Although ABO-HDN is usually a subclinical condition and less severe than Rh-HDN, a higher incidence of ABO-HDN makes it noticeable among newborn in China. There re-mains some uncertainty as to which of the IgG antibody subclasses might be more important in ABO-HDN while the effect of these subclasses is clear in RH-HDN [1][2][3] . However, currently, there are no satisfactory methods to predict ABO-HDN in the antepartum period.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, IgG1 anti-D subtypes are associated with increased severity, in contrast to IgG3 [13]. To our best knowledge, these interesting novel insights are not yet implemented in general practice.…”
Section: Introductionmentioning
confidence: 97%
“…Anti -D can be quantifi ed by comparison with a standard in an AutoAnalyser or by fl ow cytometry. IgG1 appears to be more important than IgG3 in the pathogenesis of fetal anaemia [599] . IgG1 and IgG3 anti -D both cause HDFN, IgM, IgG2, and IgG4 do not [112] .…”
Section: 'Enzyme-only' Antibodiesmentioning
confidence: 89%